2013
DOI: 10.1556/avet.2012.053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rumen-protected choline on liver composition and blood variables indicating energy balance in periparturient dairy cows

Abstract: Rumen-protected choline (RPC) was evaluated for effects on the lipid and glycogen content of the liver and metabolic variables in the blood plasma of dairy cows. Thirty-two Holstein cows were allocated into two groups (RPC group with RPC supplementation and control group without RPC supplementation) 28 days before the expected calving. Cows were fed the experimental diet from 21 days before calving until day 60 of lactation. The diet of the RPC group was supplemented with 100 g/day of RPC from 21 days prepartu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 22 publications
3
31
1
Order By: Relevance
“…In agreement with the current experiment, most laboratories have reported no effect of RPC ion supplementation on circulating concentrations of BHB in early postpartum dairy cows (Piepenbrink and Overton, 2003;Janovick Guretzky et al, 2006;Zahra et al, 2006;Zom et al, 2011;Zhou et al, 2016b) although Elek et al (2013) and Sun et al (2016) reported decreased concentration of plasma BHB in early lactation cows fed RPC ions, suggesting a possible decreased risk of subclinical ketosis. Clinical ketosis was decreased in primiparous and multiparous dairy cows fed RPC ions during the transition period on a commercial dairy farm (Lima et al, 2012).…”
Section: Plasma Metabolites In Al and R Feeding Phasessupporting
confidence: 90%
See 4 more Smart Citations
“…In agreement with the current experiment, most laboratories have reported no effect of RPC ion supplementation on circulating concentrations of BHB in early postpartum dairy cows (Piepenbrink and Overton, 2003;Janovick Guretzky et al, 2006;Zahra et al, 2006;Zom et al, 2011;Zhou et al, 2016b) although Elek et al (2013) and Sun et al (2016) reported decreased concentration of plasma BHB in early lactation cows fed RPC ions, suggesting a possible decreased risk of subclinical ketosis. Clinical ketosis was decreased in primiparous and multiparous dairy cows fed RPC ions during the transition period on a commercial dairy farm (Lima et al, 2012).…”
Section: Plasma Metabolites In Al and R Feeding Phasessupporting
confidence: 90%
“…The literature reporting the effect of supplementing RPC ions on the plasma concentration of cholesterol in early lactating dairy cows (cows in negative EB) is equivocal. Pinotti et al (2004) and Soltan et al (2012) reported an increase, Sun et al (2016) reported a decrease, and Pinotti et al (2003), Janovick Guretzky et al (2006), Zahra et al (2006), Elek et al (2013), and Zhou et al (2016a) reported no effect of supplemental RPC ions on plasma cholesterol. The effect of RPC ions on plasma cholesterol reported by Soltan et al (2012) and Sun et al (2016) were not changed when intake of methionine was altered.…”
Section: Plasma Metabolites In Al and R Feeding Phasesmentioning
confidence: 94%
See 3 more Smart Citations